ECOLOGICAL VALIDITY AND ASSESSMENT OF EXECUTIVE FUNCTION - García Molina, Alberto; Tirapu Ustárroz, Javier; Roig Rovira, Teresa (Anales de Psicología / Annals of Psychology, 2007)
Ecological validity has become an increasingly important focus in neuropsychological assessment with particular relevance for the execu-tive functions. Appropriate assessment of executive functions is critical to predict successful everyday functioning and psychosocial integration. This article reviews the research in ecological validity of neuropsychological assessment of executive function. The research suggests that many execu-tive tests have a moderate level of ecological validity when predicting everyday cognitive functioning. Environmental cognitive demands and compensatory strategy use do appear to affect the ability of neuropsy-chological tests to predict real world behaviour. This paper discusses the ecological validity of assessment of executive functions and implications for the future assessment of executive functioning. Further research is required to identify the role of several variables in determining the eco-logical validity of clinical neuropsychological tests of executive function. Some suggestions were offered for the purpose of guiding clinical re-search.